2001
DOI: 10.1103/physrevc.64.057301
|View full text |Cite
|
Sign up to set email alerts
|

Collective0+excitations and their global properties

Abstract: A simple compact correlation of the energies of the lowest 0 ϩ excitation with the yrast energy ratio R 4/2 (g.s.)ϵE(4 1 ϩ )/E(2 1 ϩ ) is found to characterize all collective nuclei, regardless of structure. This correlation can be reproduced by interacting bosom approximation calculations. Collective signature observables for the states based on 0 2 ϩ excitations indicate a different structure than for the ground state configuration but systematic inconsistencies in their global behavior and discrepancies wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 12 publications
(1 reference statement)
2
19
0
Order By: Relevance
“…The subject of many-body systems interacting by a two-body random ensemble (TBRE) has been attracting much interest since this discovery. Many authors have tried to understand the regularities exhibited by a many-body system interacting randomly and to uncover other robust properties of many-body systems [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…The subject of many-body systems interacting by a two-body random ensemble (TBRE) has been attracting much interest since this discovery. Many authors have tried to understand the regularities exhibited by a many-body system interacting randomly and to uncover other robust properties of many-body systems [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…Based on the Schrödinger-Langevin equation, [7,8,31,34,36] a phenomenological nonlinear equation was recently proposed to account for the quantum-classical transition of dissipative systems. [42] We begin by briefly reviewing the nonlinear equation given by…”
Section: Quantum-classical Transition Equation For Dissipative Systemsmentioning
confidence: 99%
“…[29] A detailed analysis of dissipative Bohmian trajectories has also been carried out in the Caldirola-Kanai model. [30] In computational applications, the Schrödinger-Langevin equation has been utilized to calculate the ground state energy and wave function of quantum systems, [31][32][33] to simulate solvent effects on the photodissociation dynamics of NOCl, [34] and to analyze the dissipative dynamics of the wave packet barrier scattering problems. [35,36] Recently, several studies have been devoted to the quantum-classical transition of physical systems from a trajectory perspective.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[28,29] It was reported that all complex quantum trajectories launched from an "isochrones" arrive on the real axis simultaneously, and these trajectories can be used to synthesize timedependent wavefunctions. [30][31][32] A complex trajectory xðtÞ5x R ðtÞ1ix I ðtÞ contains real and imaginary parts, and it is the effect of the imaginary part x I ðtÞ that allows us to use a single chaotic complex trajectory to synthesize the quantum probability. The author's previous studies [33,34] showed that a complex trajectory can be employed to envelop an ensemble of random quantum trajectories with real part representing the mean value of the trajectories and with its imaginary part representing the deviation from the mean trajectory.…”
Section: Introductionmentioning
confidence: 99%